Hybrid Bonding With Polymeric Interlayer Dielectric Layers Patterned by Nanoimprint Lithography - Sungwoo Jeon; Sohwi Lee; Hyunsik Yoon (IEEE Access)
Recent advancements in semiconductor technology have shifted the focus of innovation toward advanced packaging technologies featuring heterogeneous integration. Among these, hybrid bonding has garnered significant attention due to its potential for achieving higher integration density and reduced interconnect lengths. To alleviate thermal stress during high-temperature processes, polymeric interlayer dielectric (ILD) offers a promising solution owing to their compliant mechanical properties and strong bonding strength. In this work, we propose a simplified patterning method for polymeric dielectric layers based on thermal nanoimprint lithography (NIL). NIL enables the patterning of ILD layers using conventional polymers such as epoxy, as it does not require photoactive materials typically used in photolithography. In this study, a thermosetting epoxy resin based on diglycidyl ether of bisphenol A (DGEBA) was employed as the dielectric material. Using NIL followed by thermo-compression bonding, we achieved hybrid bonding with a $3μ $ m linewidth. The bonding strength of the Cu/epoxy interfaces was measured to lie between that of conventional Cu–Cu and epoxy–epoxy bonding, reflecting the dual contributions of metal diffusion and polymer crosslinking. These results demonstrate the feasibility of nanoimprint-based dielectric patterning for fine-pitch hybrid bonding and highlight its potential for high-density packaging and 3D integration, offering a viable alternative to traditional Through-Silicon Via (TSV)-based approaches.